STRATEGI MANAJEMEN KEPALA SEKOLAH DALAM PENGEMBANGAN BAKAT SISWA DI SD INPRES PANAIKANG - Nabila, Anugrah Rezky; Lestari, Fika; Arianti, Dini; Yuspiani, Yuspiani (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the management strategy employed by the school principal in developing student talents at SD Inpres Panaikang, encompassing planning, organizing, implementation, and supervision of the program. The research used a qualitative approach with a case study design, with data collected through observation, interviews, and documentation involving the principal, teachers, and students as informants.The results show that the principal's management strategy has been implemented systematically. Planning was carried out through the identification of student talents and the development of extracurricular programs and competition mentoring through school work meetings. Organizing was realized by forming a talent development team with task division based on teacher competencies. Implementation was reflected in regular extracurricular activities (scouting, sports, and arts) as well as intensive mentoring for talented students, while supervision was conducted through periodic monitoring and evaluation of student participation and achievement. Supporting factors included the principal's commitment, teacher support, and the involvement of parents and the school committee, while inhibiting factors included limited facilities and training time. The study indicates that the success of student talent development is determined by the principal's ability to apply management functions in an integrated and sustainable manner, making the strengthening of managerial competence and cross-party collaboration essential. These findings can also serve as a reference for other elementary schools in designing student talent development programs suited to their own conditions and resources.